Critical timing of Palmer amaranth (Amaranthus palmeri) removal in sweetpotato. (13th August 2020) - Smith, Stephen C.; Jennings, Katherine M.; Monks, David W.; Chaudhari, Sushila; Schultheis, Jonathan R.; Reberg-Horton, Chris
Abstract: Palmer amaranth is the most common and troublesome weed in North Carolina sweetpotato. Field studies were conducted in Clinton, NC, in 2016 and 2017 to determine the critical timing of Palmer amaranth removal in 'Covington' sweetpotato. Palmer amaranth was grown with sweetpotato from transplanting to 2, 3, 4, 5, 6, 7, 8, and 9 wk after transplanting (WAP) and maintained weed-free for the remainder of the season. Palmer amaranth height and shoot dry biomass increased as Palmer amaranth removal was delayed. Season-long competition by Palmer amaranth interference reduced marketable yields by 85% and 95% in 2016 and 2017, respectively. Sweetpotato yield loss displayed a strong inverse linear relationship with Palmer amaranth height. A 0.6% and 0.4% decrease in yield was observed for every centimeter of Palmer amaranth growth in 2016 and 2017, respectively. The critical timing for Palmer amaranth removal, based on 5% loss of marketable yield, was determined by fitting a log-logistic model to the relative yield data and was determined to be 2 WAP. These results show that Palmer amaranth is highly competitive with sweetpotato and should be managed as early as possible in the season. The requirement of an early critical timing of weed removal to prevent yield loss emphasizes the importance of early-season scouting and Palmer amaranth removal in sweetpotato fields. Any delay in removal can result in substantial yield reductions and fewer premium quality roots.